2021
DOI: 10.3390/healthcare9080994
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Asphyxia and Therapeutic Hypothermia in Late Preterm Infants: A Pilot Study

Abstract: Therapeutic hypothermia (THT) is the recommended treatment for neuroprotection in (near) term newborns that experience perinatal asphyxia with hypoxic-ischemic encephalopathy. The benefit of THT in preterm newborns is unknown. This pilot study aims to investigate long-term outcomes of late preterm asphyctic infants with and without THT compared to term infants. The single-center, retrospective analysis examined medical charts of infants with perinatal asphyxia born between 2008 and 2015. Long-term outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The outcomes of a recent pilot study revealed that, at 24 months of age, late preterm infants with moderate HIE after TH demonstrated age-appropriate neurodevelopmental progress. However, the study strongly advised against using the data for clinical decision making [ 42 ]. In addition, the study reported a higher mortality rate in late preterm infants (34–35 weeks of GA) with HIE as compared to infants born ≥36 weeks of GA.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of a recent pilot study revealed that, at 24 months of age, late preterm infants with moderate HIE after TH demonstrated age-appropriate neurodevelopmental progress. However, the study strongly advised against using the data for clinical decision making [ 42 ]. In addition, the study reported a higher mortality rate in late preterm infants (34–35 weeks of GA) with HIE as compared to infants born ≥36 weeks of GA.…”
Section: Discussionmentioning
confidence: 99%
“…However, treating these newborns by TH is regularly addressed in the literature4–6 and an RCT is underway in the USA (clinicaltrials.gov, no: NCT01793129). Currently, the only data are from small retrospective and/or single-centre studies7–9 and cannot reliably guide decision-making. To estimate prognosis, more information is needed.…”
Section: Introductionmentioning
confidence: 99%